1980
DOI: 10.2307/1942480
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Habitat Selection, and the Bathymetric Segregation of Two Rockfish (Sebastes) Species

Abstract: Sebastes carnatus and Sebastes chrysomelas are morphologically and ecologically similar residents of rocky reefs off the coast of California. They segregate bathymetrically, with S. chrysomelas occurring shallower than S. carnatus. Each species extended its depth distribution where its congener was removed, and no distributional changes occurred in a control area. Thus both species tolerated conditions beyond their normal depth ranges, and were limited in part of their normal depth ranges by interspecific comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 72 publications
(84 reference statements)
3
84
0
1
Order By: Relevance
“…This competitive exclusion of dusky damselfish from highquality territories by threespot damselfish has been demonstrated among congeners of other diverse taxa of fish as well. Hixon (1980) demonstrated that the surfperch Embiotoca lateralis competitively excluded E. jacksoni from shallow, food-rich substrates; Larson (1980) demonstrated that the territorial rockfish Sebastes chrysomelus was socially dominant and successfully excluded Sebastes carnatus from territories of both high food and high shelter quality. Competitive exclusion from preferred nest site habitats has been demonstrated in estuarine sticklebacks; the larger more aggressive Gasterosteus aculeatus prefers nest site habitat under the green alga Enteromorpha and successfully excludes G. wheatlandi from these areas (Cleveland 1994).…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…This competitive exclusion of dusky damselfish from highquality territories by threespot damselfish has been demonstrated among congeners of other diverse taxa of fish as well. Hixon (1980) demonstrated that the surfperch Embiotoca lateralis competitively excluded E. jacksoni from shallow, food-rich substrates; Larson (1980) demonstrated that the territorial rockfish Sebastes chrysomelus was socially dominant and successfully excluded Sebastes carnatus from territories of both high food and high shelter quality. Competitive exclusion from preferred nest site habitats has been demonstrated in estuarine sticklebacks; the larger more aggressive Gasterosteus aculeatus prefers nest site habitat under the green alga Enteromorpha and successfully excludes G. wheatlandi from these areas (Cleveland 1994).…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Howard and Harrison 1984;Suhling 1996), fish (e.g. Werner and Hall 1977;Larson 1980;Finger 1982;Bay et al 2001;Bremset and Heggenes 2001;Sone et al 2001), andterrestrial vertebrates (e.g. Douglass 1976;Hairston 1980;Bowers et al 1987), but the exact mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Optimally, the behavior of an individual would be modified to accomodate changes in habitat or the morphology of the individual. The purpose of this study was to reveal fundamental changes or consistencies in the behavior of juvenile gopher rockfish Sebastes carnatus as they settle from a pelagic existence to the substrate of the rocky reef where they become territorial.The gopher rockfish is a viviparous species whose offspring are released into the plankton in early spring (Larson 1980a). The young return to kelp forests along the central California coast, USA, when they have reached ca 30 mm standard length (Hoelzer 1987).…”
mentioning
confidence: 99%
“…obs. ).Two fundamental aspects of territorial behavior in this species are site-specificity and aggressive defence of resources (Hallacher 1977, Larson 1980a. These behaviors have not been observed in the juveniles prior to settlement.…”
mentioning
confidence: 99%
See 1 more Smart Citation